Different Complement Activation Pathways Underly Cognitive Impairment and Type 2 Diabetes Mellitus Combined With Cognitive Impairment - Li, Zhenxing; Zhang, Weiwei; Gao, Feng; Tang, Qiqiang; Kang, Dongmei; Shen, Yong (Frontiers in Aging Neuroscience, 2022)
Abstract Background: The immune response and the complement system are associated with cogni-tive impairment and diabetes mellitus, respectively. The activation of complement in these diseases occurs mainly through the classical pathway and the alternative pathway. However, the specific complement in type 2 diabetes mellitus (T2DM) and cognitive impairment are still unclear. Here, we investigated complement proteins in serum from patients with T2DM, cognitive impairment, or T2DM combined with cognitive impairment. Objective: To investigate the level of serum immune complement proteins in patients with T2DM, cognitive impairment, or T2DM combined with cognitive impairment, and associa-tions between these complement proteins and risk factors for T2DM or cognitive impair-ment. Methods: Clinical characteristics were collected in 264 participants. Luminex multiplex as-says were used to detect serum complement proteins. All statistical analyses were performed using Prism or R studio. Results: Serum levels of the complement proteins C1q, C3, C3b, and FH are different among different groups. Hyperglycemia was significantly correlated with elevated C3b or reduced C3, C1q, and FH. In addition, hyperlipidemia was positively correlated with C3, C4, C1q, and FH proteins. There was an association between C1q, C3, C4, and FH and β-pancreas cell function, whereas only FH was associated with insulin resistance. Higher serum C1q was significantly associated with the increased risk of cognitive impairment. Conclusions: Serum levels of complement proteins were affected by hyperglycemia and hy-perlipidemia. We found classical complement pathway activation mainly occurred in the cognitive impairment only group, whereas the alternative pathway may reflect T2DM and T2DM combined with cognitive impairment.